Early-Life Social Origins of Later-Life Body Weight: The Role of Socioeconomic Status and Health Behaviors over the Life Course - Pudrovska, Tetyana (2014)
Using the 1957-2004 data from the Wisconsin Longitudinal Study, we apply structural equation modeling to examine gender-specific effects of family socioeconomic status (SES) at age 18 on body weight at age 65. We further explore SES and health behaviors over the life course as mechanisms linking family background and later-life body weight. We find that early-life socioeconomic disadvantage is related to higher body weight at age 65 and a steeper weight increase between midlife and late life. These adverse effects are stronger among women than men. Significant mediators of the effect of parents' SES include adolescent body mass (especially among women) as well as exercise and SES in midlife. Yet, consistent with the critical period mechanism, the effect of early-life SES on late-life body weight persists net of all mediating variables. This study expands current understanding of life-course mechanisms that contribute to obesity and increase biological vulnerability to social disadvantage.